1980
DOI: 10.1073/pnas.77.1.485
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a basement membrane glycoprotein in embryonic kidney: possible role of laminin in morphogenesis.

Abstract: The glycoprotein laminin is found exclusively in the basement membranes of adult tissues, not in the mesenchymal stroma. We studied the appearance and distribution of laminin during the early formation of kidney tubules in mouse embryos and in an in vitro transfilter model system. In immunofluorescence using affinity-purified antibodies, the distribution of laminin showed a clear correlation, both spatially and temporally, to the early stages of tubule formation. In vivo, laminin was first detected in a puncta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(127 citation statements)
references
References 22 publications
6
121
0
Order By: Relevance
“…This is also where fibronectin, the other major matrix glycoprotein, occurs in brain tissue (Schachner et al, 1978;Paetau et al, 1980). Recently, we detected laminin production by rat astrocytes in primary culture (Liesi et al, 1983a) and found that in cultured neuroblastoma cells the ultrastructural localization of laminin (Liesi, 1983) is compatible with a role for this glycoprotein in cell-to-cell and cellto-substratum interactions (Terranova et al, 1980;Ekblom et al, 1980;Liesi, 1983). Brain injury is known to exert a glial reaction that involves a conversion of the protoplasmic astrocytes of the gray matter into reactive astrocytes positive for glial fibrillary acidic protein (GFAP) (Bignami and Dahl, 1974b;Bignami et al, 1980).…”
Section: Introductionmentioning
confidence: 60%
“…This is also where fibronectin, the other major matrix glycoprotein, occurs in brain tissue (Schachner et al, 1978;Paetau et al, 1980). Recently, we detected laminin production by rat astrocytes in primary culture (Liesi et al, 1983a) and found that in cultured neuroblastoma cells the ultrastructural localization of laminin (Liesi, 1983) is compatible with a role for this glycoprotein in cell-to-cell and cellto-substratum interactions (Terranova et al, 1980;Ekblom et al, 1980;Liesi, 1983). Brain injury is known to exert a glial reaction that involves a conversion of the protoplasmic astrocytes of the gray matter into reactive astrocytes positive for glial fibrillary acidic protein (GFAP) (Bignami and Dahl, 1974b;Bignami et al, 1980).…”
Section: Introductionmentioning
confidence: 60%
“…Thus the observation that laminin is detected in adult mouse brain only in association with capillary structures (21) may not be in contradiction with our work here. Previously, developmental changes were observed for laminin in differentiation of tubular epithelial cells from the mouse nephrogenic mesenchyme (38).…”
Section: Monensin Treatment Of the Culturesmentioning
confidence: 99%
“…Cryosections of the transplanted kidney were then immunostained for laminin and Pax2 protein expression. Laminin is expressed in the basement membrane of tubule structures in the developing kidney (Ekblom et al, 1980). Pax2 is expressed in collecting duct, metanephric mesenchyme and tubules derived from metanephric mesenchyme (Torres et al, 1995).…”
Section: Differentiation Potential Of Ra-induced Cells Using An Ex VImentioning
confidence: 99%